2014
DOI: 10.7287/peerj.preprints.595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of telenutrition in a women's weight loss program

Abstract: Objective: To evaluate the effectiveness of telenutrition versus traditional nutritional consultation for obese patients. Conclusion: Telenutrition has a failure or dropout risk factor about half values of traditional consultation with slightly statistically significant differences. This study concludes that telenutrition can support or sometimes replace the traditional consultation when developing weight loss programs in obese women. Methods

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Kuzmar IE et al, reported similar results, with no significant differences in weight loss, BMI and waist-to-height ratio (WHtR), when comparing the in-person assessment to telenutrition, in obese women. 17 Other studies have identified significant changes in anthropometric parameters, such as Huang et al, who had assessed overweight and obese patients with non-communicable diseases by using telenutrition and observed a significant BMI decrease. 18 Whereas Beleigoli et al, used a web-based software with patient feedback for 24 weeks in overweight and obese patients in comparison to non-technological interventions to assess weight loss and lifestyle changes, and indicated improvement in food consumption habits, user adherence and significant weight loss.…”
Section: Discussionmentioning
confidence: 98%
“…Kuzmar IE et al, reported similar results, with no significant differences in weight loss, BMI and waist-to-height ratio (WHtR), when comparing the in-person assessment to telenutrition, in obese women. 17 Other studies have identified significant changes in anthropometric parameters, such as Huang et al, who had assessed overweight and obese patients with non-communicable diseases by using telenutrition and observed a significant BMI decrease. 18 Whereas Beleigoli et al, used a web-based software with patient feedback for 24 weeks in overweight and obese patients in comparison to non-technological interventions to assess weight loss and lifestyle changes, and indicated improvement in food consumption habits, user adherence and significant weight loss.…”
Section: Discussionmentioning
confidence: 98%
“…Telehealth refers to remote healthcare for patients through the use of computer and telecommunication, most commonly video 2 . Telehealth is not a new approach, particularly within nutrition and weight management, but has not been widely used 2–4 . Historically, telehealth utilization has been limited, attributed primarily to logistical and financial barriers for both providers and patients—limited technology access or skills and limited reimbursement coverage from payers.…”
Section: Introductionmentioning
confidence: 99%
“…2 Telehealth is not a new approach, particularly within nutrition and weight management, © 2021 American Society for Parenteral and Enteral Nutrition but has not been widely used. [2][3][4] Historically, telehealth utilization has been limited, attributed primarily to logistical and financial barriers for both providers and patientslimited technology access or skills and limited reimbursement coverage from payers. Having to pivot to relying on this modality of care in the face of the pandemic has presented both benefits and challenges for providers, administrators, and patients.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Even before COVID pandemic, telenutrition was used as an innovative approach to adapt weight loss interventions. 3,4 In recent months, there has been a tsunami-like growth in the use of telenutrition in kidney care. We define ''renal telenutrition'' as the use of telehealth in nutritional and dietary management of kidney health and kidney disease by a registered dietitian or other nutrition professionals and expect that this new and fast expanding field will continue to evolve to become the prevailing facet of many activities that renal dietitians and other nutrition and dietetic professionals will be involved in care of patients with kidney health-related problems.…”
mentioning
confidence: 99%